there are many topics involved.
what particular problem is bothering you?
Just to start, google can provide you with many examples and solutions.
Always the best place to start on a general question like this.
CAn you help me on how to solve polynomials
5 answers
(m^2 - m - 3) + (m - 4)
f^2 x f^4
Simplify the expression
-x(7x - 8)
f^2 x f^4
Simplify the expression
-x(7x - 8)
(m^2 - m - 3) + (m - 4)
m^2 - m - 3 + m - 4 = m^2 -m+m -3-4 = m^2 + 0 -7 = m^2-7
f^2 x f^4 = f^(2+4) = f^6
Simplify the expression
-x(7x - 8) = -7 x^2 + 8 x
m^2 - m - 3 + m - 4 = m^2 -m+m -3-4 = m^2 + 0 -7 = m^2-7
f^2 x f^4 = f^(2+4) = f^6
Simplify the expression
-x(7x - 8) = -7 x^2 + 8 x
yall suckkkkkkkkkkkkkkkkkkkk
i give answers
1.D
2.A
3.A
4.D
5.C
1.D
2.A
3.A
4.D
5.C